Enzyme-responsive core-shell nanofibers based on zein/gelatin with controlled release of carvacrol for salmon preservation - Xinyang Han; Junjun Zhang; Liuzi Du; Xiaowei Huang; Xiaodong Zhai; Zhihua Li; Jiyong Shi; Xiaobo Zou (Food Chemistry, 2026)

Multifunctional pH-responsive composite films based on pectin and carbon dots@metal-phenolic networks for fried meatballs preservation - Yuqing Wu; Junjun Zhang; Xiaowei Huang; Xinai Zhang; Xiaobo Zou; Jiyong Shi (Food Hydrocolloids, 2026)

An all-in-one endoluminal acoustofluidic system enables spatiotemporal transmucosal drug delivery and barrier repair for inflammatory bowel disease - Yichen Liu; Xiaoming Zheng; Yang Qin; Jing Han; Zhiwei Cong; Shu Fan; Yan Li; Ruochen Wang; Xiaolong Guo; Qichao Huang; Xunan Jing; Yibo Liu; et al. (Chemical Engineering Journal, 2026)

Disruption of BnPHT5;1b gene enhances arsenate tolerance through increased arsenate retention in shoot cell walls of Brassica napus - Bei Han; Aosheng Jiang; Junjun Yan; Tao Wu; Bingbing Zhang; Yajie Wang; Xinyu Yang; Sheliang Wang; Zhuqing Zhao; Lei Shi (Journal of Hazardous Materials, 2026)

Improving Asian summer monsoon cloud and precipitation simulations through an ice crystal spectral relative dispersion parameterization - Xin He; Chunsong Lu; Jian Cao; Wentao Zhang; Hengqi Wang; Lei Zhu; Junjun Li; Xiaoqi Xu; Xiangjun Shi; Yuan Wang (Science China Earth Sciences, 2026)

Microwave heating uniformity enhancement based on multi-walled carbon nanotube/chitosan packaging - Yuqing Wu; Junjun Zhang; Xiaowei Huang; Xinai Zhang; Xiaobo Zou; Jiyong Shi (Food Chemistry, 2026)

Role of flow electrode chamber channel depth in charge transfer and ion migration in FCDI: Mechanistic insights and energy efficiency evaluation - Cheng Wang; Jianrui Niu; Situ Mu; Yongkun Shi; Jing Zhang; Chun Liu; Junjun Ma (Chemical Engineering Journal, 2026)

Integrating multi-stage interventions for harmful algal blooms effective management - Zhuwu Jiang; Jianxin Pan; Chengchun Shi; Xiao Yao; Huang Yu; Junjun Wang; Junjun Chen; Jyunhong Shen; Hai Yu; Wuqiang Zeng; Junlan Chen; Zhihao Lin; et al. (Journal of Environmental Management, 2026)

Multifunctional green tea-loaded alginate/ polyvinyl alcohol aerogel pads: Fabrication, characterization, sustained release, and Salmon preservation - Ke Zhang; Zhihua Li; Yaning Qin; Junjun Zhang; Naymul Karim; Sulafa B.H. Hashim; Haoyang Xu; Xiaowei Huang; Jiyong Shi; Xiaobo Zou (Innovative Food Science & Emerging Technologies, 2026)

Redox electrolyte enhances dual-anode FCDI (DA-FCDI) desalination of brackish and synchronously removal NOM - Kexin Kang; Situ Mu; Jianrui Niu; Yongkun Shi; Jing Zhang; Chun Liu; Junjun Ma (Chemical Engineering Journal, 2026)

Spatiotemporal-controlled bioinspired asymmetric Janus pad incorporating CQDs@Cu-MOF for autonomous humidity-responsive preservation of lettuce - Jianing Zhang; Junjun Zhang; Xiaowei Huang; Xiaodong Zhai; Tianxing Wang; Yang Zhang; Zhihua Li; Jiyong Shi; Xiaobo Zou (Chemical Engineering Journal, 2026)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Polyvinyl alcohol/corn starch-based indicator films integrated with roselle anthocyanins into five metal-organic frameworks for monitoring chilled pork and shrimp freshness - Xiaowei Huang; Ke Zhang; Junjun Zhang; Xiaodong Zhai; Jiyong Shi; Xiaobo Zou; Zhihua Li (Innovative Food Science & Emerging Technologies, 2025)

Identifying the optimal flow conditions of a fishway with two entrances for endemic fishes at a high-altitude hydropower station in the Tibetan Himalaya, China - Sicheng Zeng; Junjun Tan; Junjian Sun; Yuanyang Wang; Giri Raj Kattel; Xiaotao Shi (Ecological Engineering, 2025)

Evolutionary repeatability of chromatin accessibility in the hippocampus between echolocating bats and soft-furred tree mice - Luye Shi; Yuanshuo Ma; Qinyang Hua; Junjun Hao; Qin Zhang; Yaxin Ye; Lu Yang; Qi Liu; Peng Chen; Zhen Liu; Peng Shi (Science China Life Sciences, 2025)

A multiple‐behaviors virtual fish model for simulating fish trajectory in vertical slot fishways - Xiaolong Chen; Xiaotao Shi; Xingyong Deng; Majid Rasta; Junjun Tan; Yu Wang; Yongqiang Jiang; Yanqin Bai (Journal of Fish Biology, 2025)
Fishways are essential for restoring river connectivity and facilitating fish migration, necessitating ongoing research for efficiency optimization. This study developed a fish behavior model to optimize fishway efficiency cost‐effectively. The model simulates swimming trajectories of Schizothorax wangchiachii within a vertical slot fishway incorporating upstream behavior, random behavior, obstacle avoidance, and swimming speed variations. The simulated trajectory exhibits a high consistency with 20 real trajectories, achieving a trajectory overlap rate of 86.7%. This result highlights the model's ability to accurately simulate fish movements, demonstrating its significant potential to revolutionize fishway design.

Preparation of photodynamic-controlled release packaging for pork preservation and its visualization - Junjun Zhang; Jianing Zhang; Roujia Zhang; Xiaowei Huang; Zhihua Li; Xiaodong Zhai; Tingting Shen; Jiyong Shi; Xiaobo Zou (Food Chemistry, 2025)

Lemon-derived carbon quantum dots incorporated guar gum/sodium alginate films with enhanced the preservability for blanched asparagus active packaging - Jianing Zhang; Junjun Zhang; Xiaowei Huang; Xiaodong Zhai; Zhihua Li; Jiyong Shi; Remah Sobhy; Ibrahim Khalifa; Xiaobo Zou (Food Research International, 2025)

Versatile inulin/trans-ferulic acid/silk sericin nanoparticles-nourished probiotic complex with prolonged intestinal retention for synergistic therapy of inflammatory bowel disease - Yujie Zhang; Xiaojiang Zhang; Lianxi Lv; Sheng Gao; Xiang Li; Ruochen Wang; Pengqian Wang; Feiyu Shi; Junjun She; Ya Wang (Carbohydrate Polymers, 2025)

Laser-induced ZnxMnOx-rGO-C@LIG materials doped with diesel distillate for Zn-ion hybrid supercapacitors - Yuxia Wang; Hu Zou; Zhong Qi; Siyu Yang; Wenlong Jiang; Rui Zhang; Zhengchun Yang; Junjun Shi; Jie He; Peng Pan; Huayi Li (Chemical Engineering Journal, 2025)

The coupling model of random forest and interpretable method quantifies the response relationship between PM2.5 and influencing factors - Jinxing Liu; Hui Yu; Yaqing Zhang; Junjun Chen; Shiyuan Feng; Rui Guo; Feng Wang; Bo Xu; Guoliang Shi; Yinchang Feng (Atmospheric Environment, 2025)

Molecular insights into the binding mechanism of strontium and cesium on phyllosilicates with different expandability - Junjun Hou; Xiaolan Zhao; Qi Tan; Peng Wang; Xinyi Shi; Qiaohui Fan; Duoqiang Pan; Wangsuo Wu (Science of The Total Environment, 2024)

Fish community dynamics following the low-head dam removal and newly installed fish passage in a headstream tributary of Jinsha River, Southwest China - Junjun Tan; Junjian Sun; Yuanyang Wang; Huiwu Tian; Bixin Cheng; Jie Qing; Xin Yan; Gan Sun; Senfan Ke; Giri Raj Kattel; Xiaotao Shi (Science of The Total Environment, 2024)

Desalination of dye and protein by Ba2+/Ca2+ co-crosslinked alginate filtration membrane loaded on polypropylene non-woven - Ningning Gao; Qian Zhang; Yingqi Fan; Zhihui Chen; Yue Zhang; Junkui Gao; Junjun Shi; Huiguo Wang; Kongyin Zhao; Ligang Lin (Desalination, 2024)

A review of cleaner production of glass-ceramics prepared from MSWI fly ash - Xudong Chen; Yu Tan; Hui Yan; Jun Shi; Junjun Wu; Bin Ding (Journal of Environmental Management, 2024)

Evaluation of pool-and-weir fishway efficiency for the upstream spawning migration of Qinghai Lake's naked carp - Senfan Ke; Elsa Goerig; Kaiwen Pang; Huaiyao Ji; Dongqing Li; Jiawei Xu; Junjun Tan; Hongfang Qi; Xiaotao Shi (Ecological Engineering, 2024)

Co-porphyrin-based metal-organic framework for light-driven efficient green conversion of CO2 and epoxides - Jinxia Liang; Xin Jiang; Xinrui Zhang; Hao Yu; Junjun Shi; Ming Wang (Chemical Engineering Journal, 2024)

Microenvironment design strategies for enhanced CO2 electroreduction with a 60% full-cell energy efficiency - Pengtao Yue; Junjun Wu; Chaozhong Qin; Bowen Shi; Yang Wang; Yue Zhang; Yanan Zou; Jun Li; Liang Zhang; Xun Zhu; Miao Zhong; Qian Fu; et al. (Chemical Engineering Journal, 2024)

Uncertainty of canopy interception modeling in high-altitude Picea crassifolia forests of Semi-arid regions - Junjun Yang; Zhibin He; Pengfei Lin; Jun Du; Dong Shi; Meng Bai (Agricultural and Forest Meteorology, 2024)

Preparation of edible antibacterial films based on corn starch /carbon nanodots for bioactive food packaging - Yuqing Wu; Junjun Zhang; Xuetao Hu; Xiaowei Huang; Xinai Zhang; Xiaobo Zou; Jiyong Shi (Food Chemistry, 2024)

Preparation of active film based on cinnamon essential oil into β-cyclodextrin with high hydrophobic and its preservation for griskin - Yefeng Guan; Junjun Zhang; Jianing Zhang; Wenjun Song; Jiyong Shi; Xiaowei Huang; Xiaodong Zhai; Di Zhang; Zhihua Li; Xiaobo Zou (Food Control, 2024)

An observational prospective study based on a large cohort of HIV-negative neurosyphilis patients with particular reference to the Jarisch-Herxheimer reaction - Rui-Rui Peng; Juan Wu; Wei Zhao; Lin Zhu; Zhifang Guan; Xin Gu; Mei Shi; Junjun Yu; Yanchun Cheng; Pingyu Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The purpose of this study is to outline a complete picture of Jarisch-Herxheimer reaction (JHR) in the central nervous system among HIV-negative neurosyphilis patients. Methods A prospective study cohort of 772 cases with almost all stages of neurosyphilis depicted the features of JHR including occurrence rate, risk profiles, clinical manifestations, medical management and prognosis. Results The total occurrence rate of JHR was 9.3% (95% CI, 7.3-11.4%), including 4.1% (95% CI, 2.7-5.6%) with severe JHR. The reaction started 5 h after treatment initiation, peaked after 8 h, and subsided after 18 h. Patients with severe JHR experienced a longer recovery time (26 h). Patients with general paresis (OR = 6.825), ocular syphilis (OR = 3.974), pleocytosis (OR = 2.426), or a high CSF-VDRL titre (per log 2 titre increase, OR = 2.235) were more likely to experience JHR. Patients with general paresis had an 11.759-fold increased risk of severe JHR. Worsening symptoms included cognitive impairment, mania, nonsense speech, and dysphoria, while symptoms of hallucination, urination disorder, seizures, myoclonus, or aphasia appeared as new-onset symptoms. Neurosyphilis treatment did not need to be interrupted in most patients with JHR and could be reinstated in patients with seizures under supportive medication when JHR subsided. Conclusion Severe JHR displayed a 4.1% occurrence rate and clinicians should pay particular attention to patients at a higher risk of JHR. The neurosyphilis treatment regime can be restarted under intensive observation for patients with severe JHR and, if necessary, supportive medication should be initiated and continued until the end of therapy.

The influence of complex terrain on cloud and precipitation on the foot and slope of the southeastern Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Jian Li; Xiaoqing Wu; Xiaoqi Xu; Shiying Wu; Rui Hu; Xin He; Zhuangzhuang Zhou; et al. (Climate Dynamics, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Reassessing the greenhouse effect of biogenic carbon emissions in constructed wetlands - Liping Hu; Ziqian Li; Lingwei Kong; Jun Wei; Junjun Chang; Wenqing Shi (Journal of Environmental Management, 2024)

Techno-economic assessment of retrofitting indirect-heated calcium looping using coal and biomass as fuels into an existing cement plant for CO2 capture - Junjun Yin; Chao'en Li; Gabriel Paicu; Shi Su (Gas Science and Engineering, 2024)

Study of aromatic extraction from light cycle oil from the viewpoint of industrial applications - Junjun Shi; Xiaojia Wu; Guojia Yu; Lei Xi; Hu Zou; Wei Wu; Zhiyong Zhou; Zhongqi Ren (Fuel, 2024)

A ratiometric fluorescence amine sensor based on carbon quantum dot-loaded electrospun polyvinylidene fluoride film for visual monitoring of food freshness - Wenjun Song; Xiaodong Zhai; Jiyong Shi; Xiaobo Zou; Yuhong Xue; Yue Sun; Wei Sun; Junjun Zhang; Xiaowei Huang; Zhihua Li; Tingting Shen; Yanxiao Li; et al. (Food Chemistry, 2024)

Enhancement of a hybrid colorimetric film incorporating Origanum compactum essential oil as antibacterial and monitor chicken breast and shrimp freshness - Sulafa B.H. Hashim; Haroon Elrasheid Tahir; Amer Ali Mahdi; Junjun Zhang; Xiaodong Zhai; Qais Ali Al-Maqtari; Chenguang Zhou; Gustav Komla Mahunu; Zou Xiaobo; Shi Jiyong (Food Chemistry, 2024)

The Probability Density Function Related to Shallow Cumulus Entrainment Rate and Its Influencing Factors in a Large-Eddy Simulation - Lei Zhu; Chunsong Lu; Xiaoqi Xu; Xin He; Junjun Li; Shi Luo; Yuan Wang; Fan Wang (Advances in Atmospheric Sciences, 2024)

Integrated vegetation cover of typical steppe in China based on mixed decomposing derived from high resolution remote sensing data - Junjun Wu; Yi Li; Bo Zhong; Qinhuo Liu; Shanlong Wu; Changyuan Ji; Jing Zhao; Li Li; Xiaoliang Shi; Aixia Yang (Science of The Total Environment, 2023)

Potential role of selenium in alleviating obesity-related iron dyshomeostasis - Guanwen Liu; Junjun Li; Bing Pang; Yinghui Li; Fengqin Xu; Ning Liao; Dongyan Shao; Chunmei Jiang; Junling Shi (Critical Reviews in Food Science and Nutrition, 2023)

Enhancing sustainable valorization: Harmless synergistic melting treatment for high-value vitreous products from MSWI fly ash and electrolytic manganese residue - Xudong Chen; Yu Tan; Hui Yan; Jun Shi; Bin Ding; Junjun Wu (Waste Management, 2023)

Observational study of relationships between entrainment rate, homogeneity of mixing, and cloud droplet relative dispersion - Chunsong Lu; Lei Zhu; Yangang Liu; Fan Mei; Jerome D. Fast; Mikhail S. Pekour; Shi Luo; Xiaoqi Xu; Xin He; Junjun Li; Sinan Gao (Atmospheric Research, 2023)

Urbanization shifts long‐term phenology and severity of phytoplankton blooms in an urban lake through different pathways - Yuanrui Li; Juan Tao; Yunlin Zhang; Kun Shi; Junjun Chang; Min Pan; Lirong Song; Erik Jeppesen; Qichao Zhou (Global Change Biology, 2023)
Climate change can induce phytoplankton blooms (PBs) in eutrophic lakes worldwide, and these blooms severely threaten lake ecosystems and human health. However, it is unclear how urbanization and its interaction with climate impact PBs, which has implications for the management of lakes. Here, we used multi‐source remote sensing data and integrated the Virtual‐Baseline Floating macroAlgae Height (VB‐FAH) index and OTSU threshold automatic segmentation algorithm to extract the area of PBs in Lake Dianchi, China, which has been subjected to frequent PBs and rapid urbanization in its vicinity. We further explored long‐term (2000–2021) trends in the phenological and severity metrics of PBs and quantified the contributions from urbanization, climate change, and also nutrient levels to these trends. When comparing data from 2011–2021 to 2000–2010, we found significantly advanced initiation of PBs (28.6 days) and noticeably longer duration (51.9 days) but an insignificant trend in time of disappearance. The enhancement of algal nutrient use efficiency, likely induced by increased water temperature and reduced nutrient concentrations, presumably contributed to an earlier initiation and longer duration of PBs, while there was a negative correlation between spring wind speed and the initiation of PBs. Fortunately, we found that both the area of the PBs and the frequency of severe blooms (covering more than 19.8 km 2 ) demonstrated downward trends, which could be attributed to increased wind speed and/or reduced nutrient levels. Moreover, the enhanced land surface temperature caused by urbanization altered the thermodynamic characteristics between the land and the lake, which, in turn, possibly caused an increase in local wind speed and water temperature, suggesting that urbanization can differently regulate the phenology and severity of PBs. Our findings have significant implications for the understanding of the impacts of urbanization on PB dynamics and for improving lake management practices to promote sustainable urban development under global change.

Gut microbiota as a potential target for developing anti-fatigue foods - Yinghui Li; Junjun Li; Fengqin Xu; Guanwen Liu; Bing Pang; Ning Liao; Huixin Li; Junling Shi (Critical Reviews in Food Science and Nutrition, 2023)

Air conditioning system with dual-temperature chilled water for air grading treatment in data centers - Wentao Wang; Chenjiyu Liang; Fuhai Zha; Huan Wang; Wenxing Shi; Zhiyong Cui; Kaiqing Zhang; Hunlin Jia; Junjun Li; Xianting Li (Energy and Buildings, 2023)

A visual bi-layer indicator based on mulberry anthocyanins with high stability for monitoring Chinese mitten crab freshness - Xiaowei Huang; Liuzi Du; Zhihua Li; Jin Xue; Jiyong Shi; Haroon Elrasheid Tahir; Xiaodong Zhai; Junjun Zhang; Ning Zhang; Wei Sun; Xiaobo Zou (Food Chemistry, 2023)

Lattice stain dominated hydrazine oxidation reaction in single-metal-element nanosheet - Jie Shi; Qintao Sun; Wenxiang Zhu; Tao Cheng; Fan Liao; Mengjie Ma; Junjun Yang; Hao Yang; Zhenglong Fan; Mingwang Shao (Chemical Engineering Journal, 2023)

Preparation of CeVO4/BNNS catalyst and its application in oxidation desulfurization of diesel oil - Xinyu Li; Junjun Shi; Jiangang Wang; Lei Xi; Rui Sun; Fan Zhang; Xi Wu; Zhiyong Zhou; Zhongqi Ren (Fuel, 2023)

A visible colorimetric sensor array based on chemo-responsive dyes and chemometric algorithms for real-time potato quality monitoring systems - Yuqing Wu; Junjun Zhang; Xuetao Hu; Xiaowei Huang; Xinai Zhang; Xiaobo Zou; Jiyong Shi (Food Chemistry, 2023)

Study on cinnamon essential oil release performance based on pH-triggered dynamic mechanism of active packaging for meat preservation - Junjun Zhang; Jianing Zhang; Xiaowei Huang; Jiyong Shi; Arslan Muhammad; Xiaodong Zhai; Jianbo Xiao; Zhihua Li; Megan Povey; Xiaobo Zou (Food Chemistry, 2023)

Smart films of carbohydrate-based/sunflower wax/purple Chinese cabbage anthocyanins: A biomarker of chicken freshness - Sulafa B.H. Hashim; Haroon Elrasheid Tahir; Li Lui; Junjun Zhang; Xiaodong Zhai; Amer Ali Mahdi; Nosyba A. Ibrahim; Gustav Komla Mahunu; Mahmoud M. Hassan; Zou Xiaobo; Shi Jiyong (Food Chemistry, 2023)

Spectrum and mortality of opportunistic infections among HIV/AIDS patients in southwestern China - Sirun Meng; Qiao Tang; Zhiman Xie; Nianning Wu; Yingmei Qin; Rongfeng Chen; Xiaoyu Chen; Xiu Chen; Yueqi Li; Minjuan Shi; Li Ye; Hao Liang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
We describe the opportunistic infections (OIs) of HIV/AIDS to understand the spectrum, mortality, and frequency of multiple coinfected OIs among HIV/AIDS patients in southern China, where OIs are severe. We carried out a retrospective cohort study of hospitalized HIV-infected individuals at the Fourth People’s Hospital of Nanning, Guangxi, China, from Jan. 2011 to May. 2019. The chi-square test was used to analyze cross-infection; the Kaplan‒Meier analysis was used to compare mortality. A total of 12,612 HIV-infected patients were admitted to this cohort study. Among them, 8982 (71.2%) developed one or more OIs. The overall in-hospital mortality rate was 9.0%. Among the patients, 35.6% coinfected one OI, and 64.4% coinfected more than two OIs simultaneously. Almost half of the patients (60.6%) had CD4 + T-cell counts < 200 cells/μL. Pneumonia (39.8%), tuberculosis (35.3%), and candidiasis (28.8%) were the most common OIs. Coinfected cryptococcal meningitis and dermatitis are the most common combined OIs. The rate of anaemia (17.0%) was highest among those common HIV-associated complications. Multiple OIs are commonly found in hospitalized HIV/AIDS patients in southwestern China, which highlights the need for improved diagnosis and treatment.

Effect and Mechanism of Cotrimoxazole Against Talaromyces marneffei in vitro - Jie Chen; Rongfeng Chen; Wudi Wei; Fengxiang Qin; Xiu Chen; Jinhao He; Hong Zhang; Gang Wang; Minjuan Shi; Tongxue Qin; Yinlu Liao; Yuting Wu; et al. (Mycopathologia, 2022)

Relationships between Cloud Droplet Spectral Relative Dispersion and Entrainment Rate and Their Impacting Factors - Shi Luo; Chunsong Lu; Yangang Liu; Yaohui Li; Wenhua Gao; Yujun Qiu; Xiaoqi Xu; Junjun Li; Lei Zhu; Yuan Wang; Junjie Wu; Xinlin Yang (Advances in Atmospheric Sciences, 2022)

Distinctive Roles of Wnt Signaling in Chondrogenic Differentiation of BMSCs under Coupling of Pressure and Platelet-Rich Fibrin - Baixiang Cheng; Fan Feng; Fan Shi; Jinmei Huang; Songbai Zhang; Yue Quan; Teng Tu; Yanli Liu; Junjun Wang; Ying Zhao; Min Zhang (Tissue Engineering and Regenerative Medicine, 2022)

Swimming behaviour of silver carp ( Hypophthalmichthys molitrix ) in response to turbulent flow induced by a D ‐cylinder - Senfan Ke; Zhiying Tu; Elsa Goerig; Junjun Tan; Bixin Cheng; Zhimin Li; Xiaotao Shi (Journal of Fish Biology, 2022)
Turbulence is a complex hydraulic phenomenon which commonly occurs in natural streams and fishways. Riverine fish are subjected to heterogeneous flow velocities and turbulence, which may affect their movements and ability to pass the fishways. However, studies focusing on fish response to turbulent flows are lacking for many species. Here we investigate the effects of the turbulence created by a vertical half‐cylinder of various diameters (1.9, 2.5, 3.2 and 5.0 cm) on the swimming ability and behaviour of silver carp, Hypophthalmichthys molitrix . The large D‐cylinders (3.0 and 5.0 cm) create specific vorticity and reduced velocities areas in their vicinity, which favours flow refuging behaviours (FRBs) and thus increased relative critical swimming speeds ( U rcrit , BL/s) of silver carp, by comparison to free‐flow conditions and cylinders of smaller diameter (1.9 and 2.5 cm). The flow speed at which silver carp maximized FRBs such as Karman gaiting downstream of the cylinder, holding position in the bow wake or entraining on the side ranged from 40 to 70 cm s −1 , depending on fish body size. When holding station near a cylinder under optimal flow speeds, the distance between the fish and the cylinder is related to the size of the fish, but also to the size of the cylinder and the produced vortices. The optimal holding region in the drag wake of the cylinder ranged from 28 to 40 cm downstream of the centre of the cylinder, depending on the size of the fish. Smaller fish, however, tend to use the reduced velocities areas located in the bow wake of the large cylinders. We hypothesize that fish will display FRBs, including maintaining a Karman gait in turbulent flow, when the ratio of the cylinder diameter to their body length is between 1:3 and 1:4. They also match their tail beat frequency to the vortex shedding frequency of the cylinder. Our results provide a better understanding of how silver carp respond to turbulent flows around physical structures, with implications for the design of nature‐like fishways or exclusion devices in both its native and invasive ranges.

OsRhoGAP2 promoter drives inflorescence-preferential expression and confers responses to abiotic stresses in transgenic Arabidopsis - Junjun Huang; Xintian Yan; Jiajia Li; Jia Shi; Jingjing Peng; Jingyao Du; Huiwen Ge; Meina Wang; Wenjing An; Kaijie Wang; Huahua Wang; Weihong Liang (Acta Physiologiae Plantarum, 2019)

Loop-mediated isothermal amplification-lateral-flow dipstick (LAMP-LFD) to detect Mycoplasma ovipneumoniae - Jie Zhang; Junjun Cao; Mingsong Zhu; Mingguo Xu; Feng Shi (World Journal of Microbiology and Biotechnology, 2019)

Sustained-release study on Exenatide loaded into mesoporous silica nanoparticles: in vitro characterization and in vivo evaluation - Cuiwei Chen; Hongyue Zheng; Junjun Xu; Xiaowei Shi; Fanzhu Li; Xuanshen Wang (DARU Journal of Pharmaceutical Sciences, 2017)

Carnosic acid protects non-alcoholic fatty liver-induced dopaminergic neuron injury in rats - Ting Xu; Junjun Zhou; Jie Zhu; Shuai Zhang; Ning Zhang; Yan Zhao; Chunchun Ding; Xue Shi; Jihong Yao (Metabolic Brain Disease, 2017)

Decreased expression and activation of Stat3 in severe preeclampsia - Zhan Zhang; Xiaoqian Yang; Linlin Zhang; Zhenfeng Duan; Liting Jia; Peng Wang; Ying Shi; Ying Li; Junjun Gao (Journal of Molecular Histology, 2015)

Müller Glia Cells Activation in Rat Retina After Optic Nerve Injury: Spatiotemporal Correlation with Transcription Initiation Factor IIB - Yue Xu; Chen Chen; Nan Jin; Juming Zhu; Lihua Kang; Tianqiu Zhou; Junjun Wang; Aiqin Sheng; Jian Shi; Zhifeng Gu; Aimin Sang (Journal of Molecular Neuroscience, 2013)

Involvement of transcription initiation factor IIB in the light-induced death of rat retinal ganglion cells in vivo - Aimin Sang; Yue Xu; Nan jin; Tianqiu Zhou; Junjun Wang; Juming Zhu; Chen Chen; Jian Shi; Jie Shuai; Guofeng Xu; Zhifeng Gu (Journal of Molecular Histology, 2013)

Tissue distribution and expression of signaling lymphocyte activation molecule receptor to peste des petits ruminant virus in goats detected by real-time PCR - Xuelian Meng; Yongxi Dou; Junjun Zhai; Hairui Zhang; Fengchao Yan; Xiaoni Shi; Xuelong Luo; Hui Li; Xuepeng Cai (Journal of Molecular Histology, 2011)

Plus- and minus-stranded foot-and-mouth disease virus RNA quantified simultaneously using a novel real-time RT-PCR - Chaojiang Gu; Congyi Zheng; Lili Shi; Qian Zhang; Yong Li; Bin Lu; Yi Xiong; Sanpu Qu; Junjun Shao; Huiyun Chang (Virus Genes, 2007)